The Impact of Replacing Cement with a Mixture of Rice Husk Ash and Bagasse Ash on the Compressive Strength of High-Performance Concrete - Muhammad Azhari; Muttaqin Hasan; Aulia Rachman; Khirul Amna; Rafiqa Muhnita Yusputri; Vreslisawati Sagala (SAINTIS Publishing, 2025)
Bagasse ash and rice husk ash are quite smooth and have high active silica content. This forms the basis for using these ashes as substitutes for cement. In addition to being easy to find, the use of bagasse ash and rice husk ash waste is also a recent innovation to realize environmentally friendly building material technology. The purpose of this research is to determine the effect of using a combination of bagasse ash and rice husk ash as a cement substitute based on compressive strength and to compare the results with previous research. Portland cement, fine aggregate, coarse aggregate, water, superplasticizer, and a mixture of bagasse ash and rice husk ash are the materials utilized in this study as a cement replacement. The proportion variations are 0%, 5%, 10%, and 15% of the cement volume. The results of this study indicate that varying the percentage of this ash combination as a cement substitute affects the compressive strength of high-quality concrete. The most optimal compressive test results at the ages of 28 and 56 days were obtained with the 5% variation. This experienced an increase of 14.49% and 22.92% from the control concrete.